(untitled) (Medico Legal Update, 2021)
Exogenous Cushing’s syndrome is a collection of symptoms and clinical signs due to elevated levels of glucocorticoids (cortisol) in the blood because of prolonged consumption of glucocorticoid drugs. Glucocorticoids were introduced in the 1950s and have been used for anti-inflammatory treatment. Withdrawal of glucocorticoids can lead to complications of secondary adrenal insufficiency caused by suppression of the Hypothalamic-Pituitary-Adrenal (HPA) axis. Male, 28 years old, with weakness in both hands and feet throughout 3 days before admission to hospital. Other complaints include nausea (+), vomiting (+), diarrhea (-). He had been taking dexamethasone daily in the past 3 years until one month ago when he suddenly stopped. Physical examination revealed moon facies (+), striae (+) in the abdomen, and motor strength of 2 in all four extremities. Laboratory: K 2.0 mmol/L, Mg 0.8 mg/dL, GDA 64 mg/dL, Total cholesterol 240 mg/ dL, cortisol 18.67 ng/mL, ACTH 2.1 pg/mL. The patient was diagnosed with exogenous Cushing’s syndrome based on a history of long-term use of dexamethasone. Physical examination revealed moon face, buffalo hump, purplish striae, and hypertension. The patient stopped dexamethasone consumption suddenly and is consequently experiencing secondary adrenal insufficiency at the present time. As evidenced by laboratory values, there was a decrease in serum cortisol (18.67 ng/mL), as well as a decrease in serum ACTH (2.1 pg/ mL). Based on the history of dexamethasone use, physical examination, and laboratory results, this patient had exogenous Cushing’s syndrome. Sudden discontinuation of dexamethasone results in withdrawal symptoms in the form of secondary adrenal insufficiency as indicated by low cortisol and ACTH values.